2017
DOI: 10.1021/acs.jafc.7b00353
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Responsive and Highly Selective Fluorescent Probe for Bisulfite Detection in Food

Abstract: The new fluorescent probe 4-hydroxy-3-((2E,4E)-5-phenylpenta-2,4-dienoyl)-2H-chromen-2-one (probe 1) was designed and synthesized for selective detection of sulfite. The fluorescence intensity of the probe was decreased only in the presence of HSO; all other anions assessed resulted in an increased fluorescence response. Hence, probe 1 acts as a highly selective sensor for HSO. This sulfite sensitivity can also be readily monitored visually, as once treated with sulfite the solution shows a marked color change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 30 publications
0
48
0
2
Order By: Relevance
“…Advanced testing methods should be explored to obtain a lower detection limit. [40][41][42][43][44] Distribution of PHA in various fresh kidney bean cultivars PHA concentrations in fresh kidney bean cultivars were determined by hemagglutinating activity assays (Figure 1a). The standard curve is shown in (Figure 1b).…”
Section: Establish Of Pha Analysis Methodsmentioning
confidence: 99%
“…Advanced testing methods should be explored to obtain a lower detection limit. [40][41][42][43][44] Distribution of PHA in various fresh kidney bean cultivars PHA concentrations in fresh kidney bean cultivars were determined by hemagglutinating activity assays (Figure 1a). The standard curve is shown in (Figure 1b).…”
Section: Establish Of Pha Analysis Methodsmentioning
confidence: 99%
“…[4][5][6] Sulfite and bisulfite have excellent antioxidant capacity, thereby reducing the growth capacity of microorganisms; therefore, it is widely used in the food preservation industry. [7][8][9][10] At the same time, endogenous sulfites and bisulfites can also be produced in the human body, playing an important role in life activities. Medical research has shown that high concentrations of bisulfite in humans can disrupt the physiological balance, induce cardiovascular disease, nervous system diseases, and a series of allergic reactions; [11][12][13][14] therefore, the development of a simple and efficient method for the detection of sulfur dioxide derivatives has important practical significance for food safety and life microenvironment detection.…”
Section: Introductionmentioning
confidence: 99%
“…20-23 HSO 3 À plays an important role in both enzymatic and non-enzymatic reactions, and it is widely used as preservatives in foods and beverages. 24,25 However, excessive intake of HSO 3 À can not only cause damage to tissues, cells and biological macromolecules, but also can cause respiratory disease and many neurological disorders. [26][27][28] The acceptable daily intake of HSO 3 À should be less than 0.7 mg kg À1 of body weight 29 and the sulte content in foods and beverages should be less than 125 mM.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] The acceptable daily intake of HSO 3 À should be less than 0.7 mg kg À1 of body weight 29 and the sulte content in foods and beverages should be less than 125 mM. 24 In recent years, uorescent sensors have been developed using different approaches for detecting HSO 3 À , such as coordination to metal ions, 30 selective reaction with aldehyde, 31,32 selective deprotection of levulinate group 33,34 and Michael-type addition. [35][36][37] However, there are few reports on the development of chemical sensors that can sequentially identify metal ions and HSO 3…”
Section: Introductionmentioning
confidence: 99%